Decarbonization, population disruption and resource inventories in the global energy transition - Kamila Svobodova; John R. Owen; Deanna Kemp; Vítězslav Moudrý; Éléonore Lèbre; Martin Stringer; Benjamin K. Sovacool (Nature Communications, 2022)
As coal is phased out, this will have an effect on mining towns. Here the authors find that in these locations ramping up energy transition metals will be more disruptive to demographic systems than ramping down coal.